Implementasi Prinsip Dialog Lintas Agama dan Budaya sebagai Upaya Membangun Harmoni Sosial dalam Masyarakat Multikultural - Fika Fika; Novianti Novianti (Jurnal Teologi Islam, 2026)
This study aims to examine the implementation of interfaith and intercultural dialogue principles and the factors influencing their success in multicultural societies. Interfaith dialogue plays a crucial role in fostering mutual understanding, tolerance, and harmony amid diversity. This research employs a qualitative approach through literature review to explore the concepts, values, and practices of interfaith dialogue. The findings reveal that the success of dialogue is influenced by several key factors, including openness, equality, empathy, and an understanding of socio-cultural contexts. In addition, respecting differences and avoiding exclusive truth claims are essential in creating constructive dialogue. Therefore, interfaith and intercultural dialogue can serve as an effective strategy to strengthen social integration, prevent conflicts, and maintain stability and harmony in dynamic pluralistic societies